Narrative zum Gerechten Krieg im Völkerrecht - Dolezik, Joachim (Schriften zum Völkerrecht ;, 2022)
A large part of contemporary legal scholarship maintains the opinion that bellum iustum doctrine was never part of international law. However, the subject remains controversial. The work in hand attempts to cast new light on the longstanding bellum iustum -- bellum legale controversy in correspondence with the more recent narrative turn in international law. It is shown that any categorical denial of the just war doctrine in international law is flawed from the outset since law is value related.